2019
DOI: 10.1038/s41467-019-11296-5
|View full text |Cite
|
Sign up to set email alerts
|

Repeat vaccination reduces antibody affinity maturation across different influenza vaccine platforms in humans

Abstract: Several vaccines are approved in the United States for seasonal influenza vaccination every year. Here we compare the impact of repeat influenza vaccination on hemagglutination inhibition (HI) titers, antibody binding and affinity maturation to individual hemagglutinin (HA) domains, HA1 and HA2, across vaccine platforms. Fold change in HI and antibody binding to HA1 trends higher for H1N1pdm09 and H3N2 but not against B strains in groups vaccinated with FluBlok compared with FluCelvax and Fluzone. Antibody-aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 51 publications
0
69
0
3
Order By: Relevance
“…However, as seen in this study, the immune correlates may not be predictive of protection against infectious diseases. A recent study that examined the response to repetitive vaccination in humans found that there was a significant reduction in hemagglutination inhibition titers after the second immunization with an identical vaccine [47]. This study may shed light on why a high dose and repeat vaccinations do not always induce typical anamnestic responses.…”
Section: Discussionmentioning
confidence: 69%
“…However, as seen in this study, the immune correlates may not be predictive of protection against infectious diseases. A recent study that examined the response to repetitive vaccination in humans found that there was a significant reduction in hemagglutination inhibition titers after the second immunization with an identical vaccine [47]. This study may shed light on why a high dose and repeat vaccinations do not always induce typical anamnestic responses.…”
Section: Discussionmentioning
confidence: 69%
“…An example of this is shown in Figure 1A, based on a serological study done in Hong Kong in 2009 (Wu et al 2010b). However, some technical issues must be addressed, including uncertainty over the proportion of infected individuals who develop antibody at or above a certain titer ( particularly among those with subclinical infections), the delays in appearance of antibody, waning in antibody titers over the longer term, potential cross-reactions due to infections with other strains, and con- fusion of changes in antibody titer following vaccination versus infection (Chen et al 2018;Khurana et al 2019). Incidence can also be measured in closed settings such as schools and households, and outbreak investigations or transmission studies can provide valuable data on infections and illnesses.…”
Section: Incidence Of Infectionsmentioning
confidence: 99%
“…Respecto a la vacunación previa, una mayor proporción de niños sanos se vacunaba por primera vez comparado con los niños con LLA, sin alcanzar una diferencia significativa. Este antecedente concuerda con recientes evidencias respecto a que la vacuna recibida en forma repetida podría disminuir la efectividad de subsiguientes dosis de esta vacuna, reduciendo la afinidad de los anticuerpos, entre otros mecanismos 36 . Los trabajos que incluyen grupos control con niños sanos como en este estudio, también muestran una respuesta superior a la observada en niños con LLA, pero sólo en un reporte esta diferencia fue estadísticamente significativa 20,21 .…”
Section: Discussionunclassified